OS 36-01 HCaRG IMPROVES TISSUE REPAIR AFTER RENAL INJURY BY REGULATING EGFR SIGNALING. (September 2016) - Tremblay, Johanne; Campion, Carole G.; Verissimo, Thomas; Cossette, Suzanne; Matsuda, Hiroyuki; Hamet, Pavel
Abstract : Objective: Epidermal growth factor receptor (EGFR) signaling plays a dual role in hypertension-induced kidney damage. EGFR is critically involved in angiotensin II-induced renal lesions and fibrosis but is also engaged in kidney tissue repair. Consequently, targeting EGFR in renal diseases is complex because even if inhibition of EGFR activity would be beneficial, a minimal EGFR activity is needed to recover from harmful insults. Our group has identified HCaRG ( Hypertension-related, Calcium-Regulated Gene ) whose expression is increased in kidneys of hypertensive rats and mice. HCaRG overexpression in renal proximal tubules of transgenic mice increased mice survival and recovery of renal tissue integrity and function after acute kidney injury (Matsuda et al. JASN, 2013). We identified several proteins interacting with HCaRG by a yeast 2-hybrid screen of a human kidney cDNA library, including actin and proteins associated to vesicle trafficking. Our ojective is to determine whether HCaRG accelerates kidney repair by controlling EGFR signaling. Design and Method: We used renal cell lines stimulated or not with EGF and performed silencing and overexpression experiments followed by cell fractionation, confocal microscopy, western blots and co-immunoprecipitations. Results: Using renal cell lines stimulated by EGF we showed that overexpression of HCaRG enhanced EGFR tyrosine phosphorylation and activation in the early phase of EGF stimulation but accelerated EGFR degradation during prolonged EGF stimulation. On the opposite side, HCaRG silencing reduced EGFR expression and delayed its early activation by EGF. Confocal image analyses showed that HCaRG co-localized with G-actin, tubulin and EGFR at specific time points after stimulation with EGF. HCaRG co-localised with the early endosomal marker, EEA1 which is required to transport EGFR in recycling and lysosomal compartments. HCaRG also regulated ErbB2, a receptor with no known ligand that forms heterodimers with EGFR and others receptors of the family. Conclusions: HCaRG could improve tissue repair after injury by controlling EGFR signaling/trafficking.